Avaliação in vivo de um cimento de ionômero de vidro restaurador para colagem de bráquetes ortodônticos - Pimentel, Angélica Drago Marchesi (2015)
During orthodontic treatment, brackets must remain bonded to the teeth and, when necessary, removed without damaging the enamel structure. The bonding material routinely used is the composite resin (CR). The hybrid glass ionomer cement (GIC) may present as a good option to composite resins, because its fluoride release, proper adhesion to enamel and ease removal from tooth surface. However, there is only one GIC with specific indication for this function. This study aimed to verify in vivo behavior of a restorative GIC when used as orthodontic bonding material in conventional orthodontic treatments. Fifteen patients aged 11 to 27 years old (mean 16 + 4,5 anos) were selected. A total of 292 teeth were bonded, half on each arch. At the upper arch 73 teeth were bonded interchangeably with the restorative GIC Vitro Fil LC® (DFL, Rio de Janeiro, Brazil) and the orthodontic GIC Fuji Ortho LC® (GC Corp., Tokyo, Japan). At the lower arch 146 teeth were bonded with the RC Transbond XT® (3M Unitek, Monrovia, Califórnia, USA. Treatments were followed for an average period of 521.31 (±85.98) days. We evaluated: the adhesive remnant index (ARI) from unbounded and removed brackets, bracket bonding dwell time, enamel white spots after removal of the adhesive remaining. During this period, there were 12 brackets unbonded (4.1%) 9 premolars, 1 canine and 2 incisors. The unbonded premolars were prevalent in teeth bonded with the restorative GIC, althougt not statisticaly significante (p<0,05). Significant differences were found on the adhesive remnant index (ARI) for both unbonded and removed brackets between GIC (ARI=3) and CR (AIR=0 and 1). Bracket bonding dwell time were not different between bonding materials. White spots were found in two teeth bonded with CR and not in any teeth bonded with both GICs. The restorative GIC, as used in this study, remained adhered to the teeth during conventional orthodontic treatments and may be indicated as one more glass ionomer material for bonding brackets.